2003
DOI: 10.1095/biolreprod.103.017038
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Fertilization of Porcine Oocytes from Primordial Follicles by a Combination of Xenografting and In Vitro Culture1

Abstract: Our objective was to develop a method of endowing oocytes from porcine primordial follicles with full maturation and fertilizing ability as a model for ovarian xenografting of large mammals. Ovarian tissues from 20-day-old piglets, in which most of the follicles were primordial, were transplanted under the capsules of both kidneys of ovariectomized athymic mice. The host mice were treated with 5 IU of equine chorionic gonadotropin (eCG) for 10 days (eCG-10), 30 days (eCG-30), or 60 days (eCG-60) after detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 23 publications
5
64
2
3
Order By: Relevance
“…Recently, xenografting of ovarian tissues or follicles has begun to be used as a method to study oocyte growth and follicular development. Kaneko et al (2003) reported the development of primordial follicles to the antral stage at 45-75 days after xenografting ovarian tissues from 20-day-old pigs. The duration of follicular development in infant pigs in Growth of porcine primordial oocytes the present experiment is consistent with the result of Kaneko et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, xenografting of ovarian tissues or follicles has begun to be used as a method to study oocyte growth and follicular development. Kaneko et al (2003) reported the development of primordial follicles to the antral stage at 45-75 days after xenografting ovarian tissues from 20-day-old pigs. The duration of follicular development in infant pigs in Growth of porcine primordial oocytes the present experiment is consistent with the result of Kaneko et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…Primordial follicles developed to the antral stage at 45-75 days after xenografting of the ovarian tissues from 20-day-old piglets (Kaneko et al 2003). On the other hand, the development of primordial follicles from cows (Senbon et al 2003) and prepubertal pigs (Moniruzzaman & Miyano 2007) was not initiated at 6-8 weeks after xenografting.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, some studies have reported the growth from ovine and bovine preantral follicles to antral stage in precise culture conditions (Cecconi et al 1999, Itoh et al 2002. † Xenotransplantation of ovarian cortical slices from pig or cattle (Kaneko et al 2003, Senbon et al 2003 in immunodeficient SCID mice have also been attempted; some secondary follicles developed to the antral stage and the corresponding oocytes acquired the meiotic competence.…”
Section: Functional Approachesmentioning
confidence: 99%
“…Le modèle interspécifique pourrait se révéler plus efficace si la folliculogenèse elle-même était assurée au sein d'un organisme animal. Ainsi, pour court-circuiter la difficulté d'obtenir la croissance folliculaire complète in vitro, il semble possible de réaliser la première étape (la plus longue) chez l'animal, comme cela a été montré pour le porc [26]: la biopsie ovarienne porcine contenant les follicules primordiaux est d'abord transplantée sous la capsule rénale d'une souris privée de thymus et d'ovaires. La croissance folliculaire étant stimulée (par des hormones gonadotropes), des follicules à antrum apparaissent, lesquels délivrent des ovocytes dont la fécondation a pu être obtenue après MIV et FIV.…”
Section: Autres Sources D'ovulesunclassified